DRG2 Regulates G2/M Progression via the Cyclin B1-Cdk1 Complex - Jang, Soo Hwa; Kim, Ah-Ram; Park, Neung-Hwa; Park, Jeong Woo; Han, In-Seob (Molecules and cells, 2016)
Developmentally regulated GTP-binding protein 2 (DRG2) plays an important role in cell growth. Here we explored the linkage between DRG2 and G2/M phase checkpoint function in cell cycle progression. We observed that knockdown of DRG2 in HeLa cells affected growth in a wound-healing assay, and tumorigenicity in nude mice xenografts. Flow cytometry assays and [(3)H] incorporation assays indicated that G2/M phase arrest was responsible for the decreased proliferation of these cells. Knockdown of DRG2 elicited down-regulation of the major mitotic promoting factor, the cyclin B1/Cdk1 complex, but up-regulation of the cell cycle arresting proteins, Wee1, Myt1, and p21. These findings identify a novel role of DRG2 in G2/M progression.